Clinical Utility of Liquid Diagnostic Platforms in Non‐Small Cell Lung Cancer. (7th July 2016) - Levy, Benjamin; Hu, Zishuo I.; Cordova, Kristen N.; Close, Sandra; Lee, Karen; Becker, Daniel
Abstract : A firmer understanding of the genomic landscape of lung cancer has recently led to targeted, therapeutic advances in non‐small cell lung cancer. Historically, the reference standard for the diagnosis and genetic interrogation for advanced‐stage patients has been tissue acquisition via computed tomography‐guided core or fine needle aspiration biopsy. However, this process can frequently put the patient at risk and remains complicated by sample availability and tumor heterogeneity. In addition, the time required to complete the diagnostic assays can negatively affect clinical care. Technological advances in recent years have led to the development of blood‐based diagnostics or "liquid biopsies" with great potential to quickly diagnose and genotype lung cancer using a minimally invasive technique. Recent studies have suggested that molecular alterations identified in cell‐free DNA (cfDNA) or circulating tumor DNA can serve as an accurate molecular proxy of tumor biology and reliably predict the response to tyrosine kinase therapy. In addition, several trials have demonstrated the high accuracy of microRNA (miRNA) platforms in discerning cancerous versus benign nodules in high‐risk, screened patients. Despite the promise of these platforms, issues remain, including varying sensitivities and specificities between competing platforms and a lack of standardization of techniques and downstream processing. In the present report, the clinical applications of liquid biopsy technologies, including circulating tumor cells, proteomics, miRNA, and cfDNA for NSCLC, are reviewed and insight is provided into the diagnostic and therapeutic implications and challenges of these platforms. Implications for Practice: Although tumor biopsies remain the reference standard for the diagnosis and genotyping of non‐small cell lung cancer, they remain fraught with logistical complexities that can delay treatment decisions and affect clinical care. Liquid diagnostic platforms, including cell‐free DNA, proteomic signatures, RNA (mRNA and microRNA), and circulating tumor cells, have the potential to overcome many of these barriers, including rapid and accurate identification of de novo and resistant genetic alterations, real‐time monitoring of treatment responses, prognosis of outcomes, and identification of minimal residual disease. The present report provides insights into new liquid diagnostic platforms in non‐small cell lung cancer and discusses the promise and challenges of their current and future clinical use. Abstract : Technological advances in recent years have led to the development of blood‐based diagnostics or "liquid biopsies" with great potential to quickly diagnose and genotype lung cancer using a minimally invasive technique. The clinical applications of liquid biopsy technologies, including circulating tumor cells, proteomics, microRNA, and cell free DNA for lung cancer, are reviewed and insight is provided into the diagnostic and therapeutic implications and challenges of these platforms.